Protocol for Rescuing Young Cassava Embryos - Lentini, Zaida; Restrepo, Geraldine; Buitrago, María E.; Tabares, Eddie (Frontiers in Plant Science, 2020)
Embryo rescue (ER) in cassava breeding has several relevant applications, from the recovery of broad crosses to the recovery of seeds from the standard pollination program. Cassava fruit setting may drop from 100%, during the first week after pollination, to less than 40% during the second week after pollination due to the abscission of fruits depending on genotypes. Therefore, the availability of an ER protocol for early stages of embryo development, in particular during the first two weeks after pollination (prior the cotyledonary stage), could have practical implications for cassava breeding. Until now, attempts to recover cassava immature embryos at stages of development earlier than the cotyledonary stage failed. The earliest successful rescue reported in cassava is from embryos excised 32 to 36 days after anthesis (DAA). However, limited information was available regarding embryo development in cassava. This work studied and documented the stage of embryo development in histological sections of hand-pollinated ovules fixed from 1 to 30 days after anthesis (DAA). At 7 DAA, zygotes were just at the first stages of cell division (pro- embryo stage). At 14 DAA, embryos were at the pre-globular stage. Embryos at the early globular stage were observed in sections fixed at 21 DAA, and at the proper globular stage at 24 DAA. Samples at 30 DAA contained cotyledonary embryos that easily developed after ovule culture into viable plants using existing protocols. A second contribution of this work is the development of a protocol for the recovery of fully developed plants from immature embryos rescued and cultured in vitro as early as 7-14 DAA. Since embryos collected at this age are at the pro-embryo to pre-globular stage, ovary/ovule culture was necessary. A method is described whereby ovules were cultured to allow the development of pro-embryos and pre-globular stage embryos into the cotyledonary stage. Subsequently, these mature embryos were excised from the ovules to induce germination and the recovery of fully developed plants.